Annular plaques on the back. (9th January 2022) - Pruessmann, J. N.; Shimanovich, I.; Langan, E. A.; Zillikens, D.; Ludwig, R. J.; Boch, K.
Abstract : Annular lichen planus is a rare clinical variant of the lichen planus presenting with round–oval, red to brown macules and plaques with no central atrophy and slightly raised, nonscaly borders. Histopathological features are indistinguishable from typical lichen planus. Given that the accurate diagnosis relies on both the clinical presentation and typical histological features, it is important to be aware of the clinical spectrum of lichen planus. Click https://wileyhealthlearning.com/#/online-courses/6be3b20c-e9c3-40e9-8f36-bfcda6718a73 for the corresponding questions to this CME article.